2018
DOI: 10.5430/jnep.v8n8p75
|View full text |Cite
|
Sign up to set email alerts
|

Internet usage among undergraduate nursing students: A case study of a selected university in South Africa

Abstract: Background: Globally, the internet is becoming an increasingly indispensable tool in academic institutions and the workplace. Nursing students are required to use the computer and the internet to search for information and to use various software, for which computer and internet literacy are essential. Despite becoming an important tool for teaching and learning, literature reflects an under-utilization of the internet in academic and non-academic settings for a number of reasons. This article explores the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…In selected studies, the majority of nursing students were between 20–25 years, and females represented between 50.7% and 90.4% of the respondents (Bello et al 2017; Buabeng‐Andoh 2018; Elewa & El Guindy 2017; Harerimana & Mtshali 2018b; Harerimana & Mtshali 2019b; Irinoye et al 2016). One of the six studies whose population was faculty indicated the demographics of the population, and it was noted that 50% of the sample was between 40‐49 years, and the majority (84%) had a bachelor’s degree.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In selected studies, the majority of nursing students were between 20–25 years, and females represented between 50.7% and 90.4% of the respondents (Bello et al 2017; Buabeng‐Andoh 2018; Elewa & El Guindy 2017; Harerimana & Mtshali 2018b; Harerimana & Mtshali 2019b; Irinoye et al 2016). One of the six studies whose population was faculty indicated the demographics of the population, and it was noted that 50% of the sample was between 40‐49 years, and the majority (84%) had a bachelor’s degree.…”
Section: Resultsmentioning
confidence: 99%
“…Selected articles indicated that nursing students used several ICT tools such as laptops, tablets, smartphones and Internet (Elewa & El Guindy 2017; Harerimana & Mtshali 2018b; Harerimana & Mtshali 2019b; Pimmer et al 2018). Additionally, it was noted that students used ICT applications and programmes such as e‐mails, Internet search tools, word processors, Excel TM , PowerPoint TM , reference managers such as EndNote TM , Turnitin TM , data analysis software (Buabeng‐Andoh 2018; Elewa & El Guindy 2017; Harerimana & Mtshali 2019b; Nishimwe et al 2016) and social media platforms such as WhatsApp (Pimmer et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations